Pedagogical and Social Philosophy in Zambrano’s Family. Between Krausism and Zambranism - Rastrojo, José Barrientos (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This article analyses the concept of «education» in Spanish philosopher, Maria Zambrano´s, writings and those written by her father Blas Zambrano. The ideas of both are influenced by Krausism which was considered a very innovative method of learning when Blas Zambrano was teaching. Krausism creates Institución Libre de Enseñanza, Residencia de Estudiantes and Junta para la Ampliación de Estudios (its name was recovered by the Consejo Superior de Investigaciones Científicas two years ago). Some important Spanish authors and leaders had relationship with Krausism as José Ortega y Gasset, Antonio Machado, a close friend of Blas Zambrano, and Manuel Azaña, the last president of the Second Spanish Republic. Our work aims to collect lessons from Zambrano´s (father and daughter) speeches to learn how to form contemporary human beings. Furthermore, we will recover pedagogical resources buried by time and by some hidden interests.